FGTS: análise das propostas de flexibilização - Sena, Renata Moura (2009)
This thesis concerns about proposals were made in order to make flexible the use or application of the FGTS. It includes impact analysis over the government, firms and employees. The FGTS is an important device of public saving and it is able to led resources toward habitation, sewer and infrastructure areas. It is also a sort of contingency reserve available to the workers to use when them got fired or in others specific moments, according to the law. The enterprises face them like an extra cost related to the hiring process. So, it was studied features related to this fund - including management issues - to check the application possibilities and financials outcomes. In the conclusion we realized that FGTS is an important tool, it is not so simple to make its use flexible because the proposals are not complete enough to cover the impacts. And finally, its relevance increases in periods that private credits are reduced